Peran Budaya Digital dan Kreativitas terhadap Kinerja Karyawan: Apakah Krusial Bagi Perusahaan? - Efawati, Yen (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to verify the role of digital culture in improving employee performance through creativity as a mediating variable. The research was conducted in a state-owned enterprise located in Bandung, Indonesia, with a sample taken through a census, totaling 228 respondents. The research method employed a quantitative approach with an explanatory survey design. Data analysis was performed using multiple linear regression with a structural equation model, correlated with control variables including work experience, education, and age. The results indicate that employee digital culture positively impacts employee performance through individual creativity. A digitally cultured work environment can foster innovation through individual creativity, thereby enhancing productivity and adaptability to market changes. This study highlights two important aspects in creating a digital culture among employees are changes initiated from top management and the provision of adequate digital facilities and infrastructure. The study also explores how digital culture drives creativity and its impact on employee performance, incorporating control variables as explanatory factors. The complex relationships and their practical contributions to state-owned enterprises are the main focus, making this study the first to investigate the mechanisms explaining the three variables to achieve long-term competitiveness.